Quality of Life of Children with Cerebral Palsy: A Cross-Sectional KIDSCREEN study in the Southern part of the Netherlands - F. Vles, George; G.F. Hendriksen, Ruben; G.M. Hendriksen, Jose; P.M. van Raak, Elisabeth; Soudant, Dan; S.H. Vles, Johan; W.D. Gavilanes, Antonio (CNS & Neurological Disorders - Drug Targets, 2015)
Objective: To compare the quality of life (QoL) of 8-18 year old children with cerebral palsy (CP) in the Southern part of The Netherlands to a sample of European children from the general population and to investigate factors associated with possible differences. Design: A cross-sectional KIDSCREEN-52 (by-proxy version) study. Subjects/Patients: The parents of 80 out of 81 children (mean age 13.4 years, SD 2.98; 49 boys, 31 girls; Gross Motor Function Classification System (GMFCS) level 1: 21, 2: 5, 3: 16, 4: 18, 5: 20) agreed to participate. Methods: Two-sample T-tests were used to compare domain scores between groups. Regression analysis was used to identify factors associated with deviant QoL scores. Results: Parents reported significantly higher QoL for the domains of parent relation & home life and school environment. On the other hand significantly lower QoL was reported for the domains of psychical well-being, social support & peers, and social acceptance. Factors associated with deviant QoL scores were lower cognitive levels, less communication skills, and higher GMFCS levels. Conclusion: This study exposed several problem domains of QoL in children with CP living in the Southern part of the Netherlands. Several possible explanations for these findings are given. This information can be used to inform caregivers and service-providers.
Keywords: Children